Cold-evoked potentials in Fabry disease and polyneuropathy - Kersebaum, Dilara; Sendel, Manon; Lassen, Josephine; Fabig, Sophie-Charlotte; Forstenpointner, Julia; Reimer, Maren; Canaan-Kühl, Sima; Gaedeke, Jens; Rehm, Stefanie; Gierthmühlen, Janne; Baron, Ralf; Hüllemann, Philipp (Frontiers in pain research (Lausanne, Switzerland), 2024)
Fabry disease (FD) causes cold-evoked pain and impaired cold perception through small fiber damage, which also occurs in polyneuropathies (PNP) of other origins. The integrity of thinly myelinated fibers and the spinothalamic tract is assessable by cold-evoked potentials (CEPs). In this study, we aimed to assess the clinical value of CEP by investigating its associations with pain, autonomic measures, sensory loss, and neuropathic signs. CEPs were examined at the hand and foot dorsum of patients with FD ( = 16) and PNP ( = 21) and healthy controls ( = 23). Sensory phenotyping was performed using quantitative sensory testing (QST). The painDETECT questionnaire (PDQ), FabryScan, and measures for the autonomic nervous system were applied. Group comparisons and correlation analyses were performed. CEPs of 87.5% of the FD and 85.7% of the PNP patients were eligible for statistical analysis. In all patients combined, CEP data correlated significantly with cold detection loss, PDQ items, pain, and autonomic measures. Abnormal CEP latency in FD patients was associated with an abnormal heart frequency variability item ( = -0.684; adjusted = 0.04). In PNP patients, CEP latency correlated significantly with PDQ items, and CEP amplitude correlated with autonomic measures ( = 0.688, adjusted = 0.008; = 0.619, adjusted = 0.024). Furthermore, mechanical pain thresholds differed significantly between FD (gain range) and PNP patients (loss range) ( = 0.01). Abnormal CEPs were associated with current pain, neuropathic signs and symptoms, and an abnormal function of the autonomic nervous system. The latter has not been mirrored by QST parameters. Therefore, CEPs appear to deliver a wider spectrum of information on the sensory nervous system than QST alone.